(untitled) (Journal of Current and Advance Medical Research, 2014)
Hypothyroidism is one of the common endocrine disorders. Causes are variable. It can be congenital or acquired. Congenital hypothyroidism termed as cretinism. Lingual thyroid is one of the rare congenital anomaly causing hypothyroidism. Its clinical incidence varies between 1/3000 and 1/10,000. Up to 70% of patients with lingual thyroid have hypothyroidism and 10% suffer from cretinism. Here a 14 year old short stuttered obese female present with the complaints of voice change & weight gain. Biochemically she was diagnosed as hypothyroid. To find out the cause it was detected the gland was not in normal position but in the lingual position which was detected by SPECT CT Tc-99m isotope thyroid scan. The patient was treated with levo-thyroxin accordingly and was improved. DOI: http://dx.doi.org/10.3329/jcamr.v1i2.20518 Journal of Current and Advance Medical Research Vol.1(2) 2014: 42-48